Motives of employed and unemployed volunteers’ participation in SEA Games 2017 / Nur Alissa Mahmood - Mahmood, Nur Alissa (2021)
The present study investigated the motives of employed and unemployed volunteers participation in SEA Games 2017. Quantitative analysis was used based on questionnaire conducted with randomly selected volunteers in SEA Games (N=372) for this study. Understanding (M = 4.53) had the highest mean among the volunteers' motivations, followed by value (M = 4.46). The result show that no statistically significant difference in general volunteer motivation (t =.650, p > 0.05) based on work position. Between employed and unemployed volunteers, there was a significant difference in terms of value (t = 2.503, p 0.05) and career (t = -1.049, p 0.05) for the sub-dimension of volunteer motivation. This findings is critical to comprehend volunteer intentions in order to assist hosting organizations in delivering appropriate results that benefit two or more parties that are directly and indirectly involved in volunteerism. The best understanding of volunteer intentions could contribute to increased knowledge of the benefits of volunteering and increased volunteer retention in the future.